Morphology-controlled fabrication of nano Ag/poly (vinyl pyrrolidone) composites and their effect on electric conductive properties of UV ink. (19th December 2016) - Chen, G. X.; Chen, Y. Y.; Cui, Y. Y.; Chen, Q. F.; Chen, T.; Yang, Y.
Abstract : To meet an increasing market demand of conductive ink which is applicable to wide range of substrates, ultraviolet (UV) curing technique combined with nano-silver materials was used to fabricate UV electric conductive ink. Firstly, both silver nano-particles ( AgNPs ) and silver nano-wires ( AgNWs )/poly (vinyl pyrrolidone) (PVP) composites were synthesized. An ethanol solution-phase approach using hydrazine hydrate as a reducing agent was presented for an easy synthesis of large-scale AgNPs with an average diameter of 35 nm. AgNWs with diameter of 40 nm and length up to over 10 μm were synthesized by polyol method. In AgNWs synthesis process, the main influencing factors such as the molar ratio of PVP to silver nitrate, the reaction time and PVP of different degree of polymerization were investigated. Finally, nano Ag/PVP composites, polyurethane acrylate, photoinitiator 1173 and solvents were used to fabricate UV electric conductive ink, which had an electrical conductivity on paper as high as 2.1 × 10 5  S/m.